Zeitgenössische Möbiliar aus Flandern : Design aus Flandern. (Köln : Das Belgische Haus Köln, 1994)
Casimir ; De Rudder, Nora ; De Swerts, Rafaël ; Dewulf, Koenraad ; Mecibah, Idir ; Meylaerts, Dirk ; Ramael, Luc ; Reuvis, Patrick ; Patriské ; Supply, Marc ; Lahtua, Anneli ; De Velde, Willy A.D.D. Van ; Van Geele, Rudy ; Van Severen, Fabiaan ; Van Severen, Maarten ; Van Troost, Anthony ; Wittocx, Herman
biografie
Duits
boek
Keywords: België; Vlaanderen